Whole Slide Images and Digital Media in Pathology Education, Testing, and Practice: The Oklahoma Experience - Kar-Ming Fung; Lewis A. Hassell; Michael L. Talbert; Allan F. Wiechmann; Brad E. Chaser; Joel Ramey (Analytical Cellular Pathology)
Examination of glass slides is of paramount importance in pathology training. Until the introduction of digitized whole slide images that could be accessed through computer networks, the sharing of pathology slides was a major logistic issue in pathology education and practice. With the help of whole slide images, our department has developed several online pathology education websites. Based on a modular architecture, this program provides online access to whole slide images, still images, case studies, quizzes and didactic text at different levels. Together with traditional lectures and hands-on experiences, it forms the back bone of our histology and pathology education system for residents and medical students. The use of digitized whole slide images has a.lso greatly improved the communication between clinicians and pathologist in our institute.